Cognitive and motor function in developmental coordination disorder. (8th August 2020) - Wilson, Peter; Ruddock, Scott; Rahimi‐Golkhandan, Shahin; Piek, Jan; Sugden, David; Green, Dido; Steenbergen, Bert
Abstract : Aim: To analyse the development of motor skill and executive function in school‐aged children with and without developmental coordination disorder (DCD). Method: Using a longitudinal design, 186 children (86 males, 100 females) aged 6 to 11 years at Time 1 were tested over a 2‐year period, 52 of whom were diagnosed with DCD at Time 1 (27 males, 25 females; mean age 8y 5mo, SD 1y 6mo) using DSM‐5 criteria. The McCarron Assessment of Neuromuscular Development assessed motor status at Time 1 and at 2‐year follow‐up (Time 2). Executive function was assessed using a well‐validated measure, the Groton Maze Learning Test. Results: The DCD cohort at Time 1 had moderate incidence of executive function deficit (41%). Most importantly, at a group level, children with persisting DCD (across Times 1 and 2) also showed significantly lower levels of executive function than children with typical motor development at both time points. At an individual level, around 26% of children in this group had persisting executive function deficits relative to normal ranges of performance. Interpretation: Children with persisting DCD are at significant risk of executive function issues. The combination of motor and cognitive issues as a potential risk factor in the longer‐term development of children is discussed. What this paper adds: Around half of children initially diagnosed with developmental coordination disorder (DCD) had the same diagnosis at 2‐year follow‐up. 41% of children with DCD have impaired executive function. Children with persisting DCD show poorer executive function than those with typical motor development or remitting DCD. What this paper adds: Around half of children initially diagnosed with developmental coordination disorder (DCD) had the same diagnosis at 2‐year follow‐up. 41% of children with DCD have impaired executive function. Children with persisting DCD show poorer executive function than those with typical motor development or remitting DCD. This article is commented on by Vaivre‐Douret on page 1235 of this issue.